Efek Pemberian Oksigen Hiperbarik Pada Efektivitas Ekstrak Cacing Tanah (Lumbricus terrestris) Terhadap Pertumbuhan Salmonella Typhi Secara In Vitro - VARIDIANTO YUDO TJAHJONO; RETNO BUDIARTI; PRAWESTY DIAH UTAMI (Universitas Hang Tuah, 2022)
Background: Typhoid fever is an infectious disease of the small intestine caused by the bacterium Salmonella typhi, and causes a fairly high mortality rate. These bacteria have developed resistance to many antibiotics. Earthworm extract (ECT) has been widely used as an alternative to treat typhoid fever. Hyperbaric oxygen therapy (OHB) has been used to treat various diseases and can suppress the growth of bacteria. Objective: To determine the effect of hyperbaric oxygen (OHB) 3 ATA on the effectiveness of earthworm (Lumbricus terrestris) extract on the growth of Salmonella typhi in vitro. Methods: This experimental study used the post-test only control group design method. Thirty-six samples of S.typhi bacteria in liquid medium (broth) were divided into four groups. The first group (K-) was not given any treatment, the second group (P1) was given earthworm extract, the third group (P2) was given hyperbaric oxygen 3 ATA, and the fourth group (P3) was given a combination of earthworm extract and hyperbaric oxygen 3 ATA. The results of bacterial growth in each group were calculated in colony forming units (CFU) / ml and analyzed statistically. Results: The growth of S.typhi bacteria in the first group (K-) was 108.51 x 106 CFU/ml, the second group (P1) was 483 CFU/ml, the third group was 1.4 x 106 CFU/ml, and the fourth group (P3) was 215 CFU/ml. The fourth group (P3) had the smallest number of bacterial growth and had a significant difference compared to the first (P1) and third (P3) groups (p = 0.001; p < α ; α = 0.05), but the difference was not significant compared to the second group (P1 ) (p = 0.308; p > α; α = 0.05). Conclusion: Giving earthworm extract (ECT) with hyperbaric oxygen (OHB) 3 ATA (combination) was most effective in inhibiting the growth of Salmonella typhi bacteria compared to giving earthworm extract (ECT) alone or giving hyperbaric oxygen (OHB) 3 ATA alone.